Writing with scissors American scrapbooks from the Civil War to the Harlem Renaissance - Garvey, Ellen Gruber (New York ; Oxford : Oxford University Press, 2013)
Featuring over 50 rare and hard-to-find illustrations, 'Writing with Scissors' presents a fascinating cultural history of scrapbooks in America.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: Scrapbooks -- United States -- History; Scrapbooking -- United States -- History